Adiposity, fat-free mass and incident heart failure in 500 000 individuals - Oguntade, AS; Taylor, H; Lacey, B; Lewington, S (BMJ Publishing Group, 2024)
Background and aims The independent role of body fat distribution and fat-free mass in heart failure (HF) risk is unclear. We investigated the role of different body composition compartments in risk of HF.